Summers at the Saint [large type] - Andrews, Mary Kay, 1954- (Thorndike Press large print dynamic drama., 2024)
"Everyone refers to the St. Cecelia as "the Saint." If you grew up coming here, you were a Saint. If you came from the wrong side of the river, you were an Ain't. Traci Eddings was one of those outsiders whose family wasn't rich enough to vacation here. But she could work here. One fateful summer she did, and married the boss's son. Now, she's the widowed owner of the hotel, determined to see it return to its glory days. But new information about a long-ago drowning at the hotel threatens to come to light, and a tragic death brings Traci to the brink of despair. It will take all the guts she has to see wrongs put to right, to see guilty parties put in their place"--